Exploring online health information quality criteria on social media: a mixed method approach - Hossein Ghalavand; Abdolahad Nabiolahi (BMC, 2024)
Abstract Purpose This article outlines a research study that ranked health information quality criteria on social media from experts' perspectives. Methodology A mixed-method approach (qualitative-quantitative) used in current research. In the qualitative phase a literature review explored existing dimensions for evaluating social media content quality, focusing on identifying common dimensions and attributes. Furthermore, a quantitative method involving experts was utilized to rank the health information quality criteria for social media. Results The findings indicated various dimensions of health information quality in the literature. Out of 17 criteria, accuracy, credibility, and reliability had the highest ranks, while originality, value-added, and amount of data had the lowest ranks, respectively, according to experts. Conclusion The endeavor to bolster the dissemination of reliable health information on social media demands a sustained commitment to enhancing accountability, transparency, and accuracy, ensuring that users have access to information that is not only informative but also trustworthy.